2020
DOI: 10.1093/eurpub/ckaa206
|View full text |Cite
|
Sign up to set email alerts
|

The influence of marital status and partner concordance on participation in colorectal cancer screening

Abstract: Background Colorectal cancer screening program using a fecal immunochemical test aims to reduce morbidity and mortality through early detection. Although screening participation is free-of-charge, almost 40% of the invited individuals choose not to participate. To bring new insight into how non-participation can be identified and targeted, we examined the association between marital status and screening participation; with a focus on partner concordance in participation and sex differences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…In the publicly funded screening programmes in Denmark, Finland and Spain, uptake in faecal‐based screening was shown to increase by increasing age, 5,7,8 but, similarly to our findings, it decreased from the top participation rate after reaching 70 years of age in Denmark 5 . A common feature with our and the other European studies is that participation in faecal‐based screening was higher in women than men 8,19,20 . We observed that the difference in uptake between males and females was stronger in the FIT than in the sigmoidoscopy arm.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the publicly funded screening programmes in Denmark, Finland and Spain, uptake in faecal‐based screening was shown to increase by increasing age, 5,7,8 but, similarly to our findings, it decreased from the top participation rate after reaching 70 years of age in Denmark 5 . A common feature with our and the other European studies is that participation in faecal‐based screening was higher in women than men 8,19,20 . We observed that the difference in uptake between males and females was stronger in the FIT than in the sigmoidoscopy arm.…”
Section: Discussionsupporting
confidence: 89%
“…5 A common feature with our and the other European studies is that participation in faecalbased screening was higher in women than men. 8,19,20 We observed that the difference in uptake between males and females was stronger in the FIT than in the sigmoidoscopy arm. Similarly, the Spanish COL-…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Finally, other factors influencing cancer screening behavior such as having a usual source of care ( 72 ), access to transportation ( 73 , 74 ), health literacy ( 75 , 76 ), doctor's recommendation ( 77 , 78 ), and other socioeconomic factors (e.g., marital status, education, income, poverty level, home rental, etc.) ( 79 81 ) were not measured due to data limitation and can be controlled in future studies.…”
Section: Limitationsmentioning
confidence: 99%
“…An unmarried status, including being widowed, divorced, or single, is associated with increased mental health problems, cardiovascular diseases, coronary heart disease, and stroke-related death [ 5 , 6 ]. Regarding malignancies, a strong association between marital status and participation in cancer screening has been reported, and participation is even higher in married individuals with a participating partner [ 7 ]. In married individuals, cancer is detected earlier, while unmarried individuals are more likely to be diagnosed at an advanced stage and/or be untreated despite diagnosis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%